Organizational Communications in The Investigation of The Kanjuruan Tragedy on Online News Framing - Muhamad, Pagi; Dwinarko, Dwinarko; Tabrani Sjahfrizal; Saeful Mujab (MSJ : Majority Science Journal, 2025)
The Kanjuruan tragedy that occurred at the Malang Football Stadium, in East Java is one of the tragedies events caused by the results of the match between Persebaya Surabaya and Arema Malang, which was held on October 1, 2022. As a result of the tragedy, 125 people died. The purpose of this study is to determine the responsibility of actors through organizational communication in the investigation of the Kanjuruan Football Stadium tragedy, in framing online mass media news. The theories used in this study are organizational network theory with a descriptive qualitative research approach and a framing method with narrative analysis of online media news framing texts. The results showed that mitigation and investigation in news framing is a frame of social action for a network of organizational actors that micro-involves individuals, involves organizations, and macro-involves governments and external organizations. The text is meaningful and positive in the framing of President Joko Widodo's news with the President of FIFA in mitigating events by cooperating transformation through organizational networks. The role of organizational communication network systems in coordinating the activities of organizational actors in integrating community security for network business stakeholders.